2011
DOI: 10.1111/j.1468-3083.2011.03988.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the seasonal onset of chronic venous leg ulcers and climatic factors

Abstract: The onset of chronic leg ulcers caused by CVI and mixed arterial and venous disorders in our patient population showed significant seasonal variations and demonstrated an inverse relationship to temperature. In summary, climatic factors appear to play an important role in the onset of chronic leg ulcers. Climatic factors may therefore need consideration in future clinical investigations and in the development of prophylactic therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
1
8
1
2
Order By: Relevance
“…Klode et al. reported that the occurrence of chronic leg ulcers of vascular origin shows significant seasonal variability in Germany, with an increased incidence during cold months .…”
Section: Discussionmentioning
confidence: 99%
“…Klode et al. reported that the occurrence of chronic leg ulcers of vascular origin shows significant seasonal variability in Germany, with an increased incidence during cold months .…”
Section: Discussionmentioning
confidence: 99%
“…An increased pressure in the venous pressure causes a retrograde elevation of pressure into the venules (thinner veins) of the skin. This leads to continuous elevated ambulatory venous pressures (as known commonly venous hypertension) that have been related to development of leg ulcers in advanced stages [18].…”
Section: Anatomy Of the Venous Systemmentioning
confidence: 99%
“…Ils ont montré que le froid hivernal favorise l'affection par les ulcères, alors que la chaleur estivale contribue à leur aggravation. De même, le vieillissement accentue la vulnérabilité de la surface cutanée et la rend plus sensible aux effets de la température extérieure (Klode et al, 2011).…”
Section: Echogéo 38 | 2016unclassified